A correlative study of homocysteine levels and dementia: an Indian perspective - Iqbal, Roshan; Harsha, S.; C., Nemichandra S.; Paneyala, Shasthara; Colaco, Vimala C. (International Journal of Research in Medical Sciences, 2021)
Background: The prevalence of dementia is increasing worldwide and with India experiencing an epidemiological transition with increasing ageing population, the prevalence in India is expected to double by 2030 adding to the already high burden of significant health care costs and caregiver fatigue. Indian population has a higher burden of elevated homocysteine levels due to multiple factors. However, studies correlating the homocysteine levels and severity of dementia in the Indian subcontinent is lacking. This study is aimed to analyse the diagnostic utility of serum total homocysteine in dementia and to examine the association between serum total homocysteine levels and severity of dementia. Methods: This was a cross-sectional hospital-based study on patients attending neurology out-patient department who satisfied the DSM-V criteria. Each participant underwent an interview of general health and function followed by a standard assessment including medical history, physical and neurological examination as well as a neuropsychological battery. Results: A total of 30 patients fulfilling the DSM-Vcriteria for Dementia were included in the study. Increasing S. Homocysteine levels were associated with lower neuropsychological compound scores with MMSE score of 20.78±2.98 and ACE-3 score of 77.40±5.60 in patients with Serum Homocysteine less than 22 Umoles/L and 18.85±2.50 and 75.55±5.06 respectively in patients with serum homocysteine levels above 22 Umoles/L. However, there was no statistically significant correlation between neurocognitive scores and serum homocysteine levels (p value 0.06 for MMSE and 0.19 for ACE-3). Also, no correlation was found between severity of dementia and serum homocysteine levels with p≥0.05 and Pearson’s correlation coefficient r=0.06. Conclusions: This study shows no significant association between serum total homocysteine levels and severity of dementia. Thus, the association of homocysteine as an independent risk factor with the diagnosis and severity of dementia needs to be re-evaluated as it might undermine the multiple mechanisms underlying the pathogenesis of dementia.